A unifying experimental design for dissecting tree genomes. (August 2015) - Sun, Lidan; Zhu, Xuli; Zhang, Qixiang; Wu, Rongling
Highlights: Linkage mapping and association analysis are used separately, limiting their potential power. We integrate these two approaches into an organizing framework through an open-pollinated design. The integrative model strengthens population and quantitative genetic studies for evolutionary inference and high-resolution gene mapping. The design particularly suits genome dissection of forest trees given their undomesticated populations. Abstract : Linkage mapping and association mapping are adopted as an approach of choice for dissecting complex traits, but each shows a limitation when used alone. We propose an open-pollinated (OP) family design to integrate these two approaches into an organizing framework. The design unifies the strengths of population and quantitative genetic studies for evolutionary inference and high-resolution gene mapping. It particularly suits genome dissection of forest trees given their extant populations that are mostly undomesticated.